2016
DOI: 10.1002/wrna.1351
|View full text |Cite
|
Sign up to set email alerts
|

The evolving world of small RNAs from RNA viruses

Abstract: RNA virus infection in plants and invertebrates can produce virus-derived small RNAs. These RNAs share features with host endogenous small interfering RNAs (siRNAs). They can potentially mediate RNA interference (RNAi) and related RNA silencing pathways, resulting in specific antiviral defense. Although most RNA silencing components such as Dicer, Ago2, and RISC are conserved among eukaryotic hosts, whether RNA virus infection in mammals can generate functional small RNAs that act in antiviral defense remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 108 publications
(238 reference statements)
0
17
0
1
Order By: Relevance
“…Virus infection in plants is usually associated with the accumulation of virus-derived small interfering RNAs (vsiRNAs) that play essential roles in antiviral RNA silencing defense by degrading viral RNA in a sequence-specific manner ( Llave, 2010 ; Zhang et al, 2015 ; Li M.L. et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Virus infection in plants is usually associated with the accumulation of virus-derived small interfering RNAs (vsiRNAs) that play essential roles in antiviral RNA silencing defense by degrading viral RNA in a sequence-specific manner ( Llave, 2010 ; Zhang et al, 2015 ; Li M.L. et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of antiviral RNA silencing Dicer-2 recognizes and cleaves dsRNA structures (generated during virus replication) into siRNAs, from which one strand activates a RISC complex containing AGO2 to surveil the cell for ssRNA with sequence complementarity to the siRNA [ 14 , 86 , 87 , 88 ]. The pathway also includes other proteins such as Loquacious (Loqs, which increases affinity of Dicer-2 to dsRNA), R2D2 (aids siRNA loading in AGO2 and RISC assembly), component 3 promoter of RISC (C3PO, facilitates AGO2 endonucleolytic cleavage of the siRNA passenger strand) and HEN1 (stabilizes the guide strand by methylating its 3′ terminal nucleotide) (a deeper review of arthropod RNA silencing can be found in [ 89 , 90 , 91 ]). Similar to plant-infecting viruses, several arthropod-infecting viruses have been shown to counteract arthropod antiviral RNA silencing by expressing RSS proteins that can target different steps of the RNA silencing machinery.…”
Section: Arthropod Rna Silencing and Arbovirusesmentioning
confidence: 99%
“…Роль внРНК рассматривалась неоднократно в обширных обзорах в разных аспектах [5,11,19], и в обсуждении полученных нами результатов будут затронуты другие аспекты их возможных функций. Выявленные в настоящем исследова-нии в геномах вирусов 3 категории последова-тельностей -аутоКП, ГП и КП -потенциально могут играть роль в различных процессах жиз-ненного цикла вирусов и соответственно влиять на течение инфекционного процесса, который они вызывают у человека.…”
Section: Discussionunclassified